The Impact of the COVID-19 Pandemic on Consumer Behavior—Evidence From China's Stock Market - Lu, Zhou; Zhu, Linchuang; Li, Xiaoxin; Li, Zhenhui (Frontiers in Public Health, 2022)
The COVID-19 pandemic has dramatically reshaped consumers' grocery shopping behavior. Meanwhile, change in consumer shopping behavior might further exert a considerable and far-reaching impact on the food retail industry. Although the existing literature provides investigation on the impact of the pandemic on the retail industry, very few studies discuss the impact of changes in consumer shopping behavior on the stock market performance of the retail industry. This paper investigates selected food retailers listed in China's stock market. To overcome the problems of the Chow test, the Quandt-Andrews test was used to identify the dates of breakpoints of structural change in the stock price performance of those selected companies. The results suggest that there has indeed been an industry-wide structural change in the stock market performance during the pandemic. The study found that the dates of breakpoints for the selected companies were concentrated in the first half of 2020, when China was hit by the Covid-19 pandemic the most. Our survey shows that under strict epidemic prevention and control measures, consumers have gradually adapted to the new normal of epidemic prevention to a certain extent, established safety awareness, and changed their consumption behavior. Our study on stock price data implies that Chinese consumers experienced a shift from physical store offline purchases to online purchasing model.